2021
DOI: 10.3390/ijms22083939
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Chemicals and Infectious Diseases: From Endocrine Disruption to Immunosuppression

Abstract: Endocrine-disrupting chemicals (EDCs) are hormonally active compounds in the environment that interfere with the body’s endocrine system and consequently produce adverse health effects. Despite persistent public health concerns, EDCs remain important components of common consumer products, thus representing ubiquitous contaminants to humans. While scientific evidence confirmed their contribution to the severity of Influenza A virus (H1N1) in the animal model, their roles in susceptibility and clinical outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 129 publications
0
7
0
Order By: Relevance
“…Several inflammatory mediators have been shown to take part in both the initiation and progression of cancer. 26,27 Even though GRP and GRPR cell surface receptors trigger inflammatory pathways, they interfere with other relevant growth factor pathways such as TGF-1β, which promotes matrix deposition and encourages the secretion and activation of the proteolytic enzymes MMP-2 and MMP-9. 22 The increase in inflammatory cytokines stimulates the expression of adhesion molecules in cancer patients leading to the interaction between metastatic cells and target organs.…”
Section: Discussionmentioning
confidence: 99%
“…Several inflammatory mediators have been shown to take part in both the initiation and progression of cancer. 26,27 Even though GRP and GRPR cell surface receptors trigger inflammatory pathways, they interfere with other relevant growth factor pathways such as TGF-1β, which promotes matrix deposition and encourages the secretion and activation of the proteolytic enzymes MMP-2 and MMP-9. 22 The increase in inflammatory cytokines stimulates the expression of adhesion molecules in cancer patients leading to the interaction between metastatic cells and target organs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on literature reviews, we selected 25 candidate mediators of modifiable cardiometabolic risk factors (for an overview of the process of identifying the candidate mediators see Figure S1), 14–41 which may lie on the pathways from education to hypertension or cardiovascular disease and with available genetic instruments derived from GWASs, including adiposity traits (body mass index [BMI], 14 waist-to-hip ratio [WHR], 15 body fat percentage [BF%], 16 waist circumference, 17 childhood obesity 18 ), lipids (low-density lipoprotein cholesterol, 19 high-density lipoprotein cholesterol [HDL-C], 19 triglycerides, 19 total cholesterol 20 ), glucose metabolism-related traits (fasting insulin 21 and fasting glucose 22 ), urinary biomarkers (urinary sodium, 23 urinary potassium, 23 urinary albumin, 24 urinary sodium-potassium ratio 25 ), physical activity and sedentary behaviors (moderate to vigorous physical activity, 26 watching TV, 27 computer using 27 ), stress-related traits (major depression 28 and insomnia 29 ), smoking and dietary behaviors (smoking initiation, 30 smoking heaviness, 31 alcohol drinking, 32 coffee consumption 33 ), and socioeconomic factor (total household income). 41 The detailed information of the epidemiological evidence for the relationship between the 25 candidate mediators and hypertension or blood pressure is shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, however, the hypothesis has begun to emerge that this condition may be associated with a state of cellular immune depletion which includes monocytes, dendritic cells, CD4 + T cells, CD8 + T cells, B cells, and NK cells. These data suggest that severe COVID-19 is a state of immunosuppression similar to the well-known sepsis-induced immunosuppression [61,62]. In particular, a recent study by Remy et al [63] showed that the immuno-suppression observed in these subjects is even more profound than in critically ill patients with sepsis from other causes.…”
Section: Discussionmentioning
confidence: 71%